Deep Learning-Based Prediction Model for Drug-Target Interactions - Mohapatra, Puspanjali; Palei, Shantilata; Sinha, Aryan; P. Subham; Adarsh Kumar (Journal of Advanced Computer Science & Technology, 2024)
This paper comprehensively studies deep learning approaches for drug-target interaction (DTI) prediction in drug discovery. We evaluate the performance of convolutional neural networks (CNNs), recurrent neural networks (RNNs), and transformers on DTI prediction tasks. Our results demonstrate that the CNN model consistently outperforms both RNN and transformer models in accuracy. Additionally, we investigate the impact of transfer learning on DTI model performance, showing that pre-trained fine-tuning significantly enhances the results. These insights contribute to selecting and optimising deep learning models for DTI prediction, thereby advancing drug discovery efforts. Notably, our findings highlight the potential of combining CNNs with the BindingDB dataset and utilizing transformers as pretrained models for real-world DTI cases.